FLACC 2004 :FLACC Centrum voor kunsten en beeldcultuur : Jaarboek 2004. - Brijs, Lief; Luyckx, Filip; Nys, Tom; Patteeuw, Roland; Smets, Francis; Teerlinck, Hilde; Van Bellingen, Stef; Van Rossem, Patrick; Vietà, Mayte; Weyns, Sara; FLACC, Genk (Genk : FLACC - Centrum voor kunsten en beeldcultuur Genk, 2004)
Almarcequi, Lara ; Arts, Fred ; Bailly, Virginie ; Bieman, Ursula ; Coolen, Caroline ; Coro, Pier Paolo ; Crollet, Ingrid ; De Decker, Koen ; Demare, Mirta;Dias & Riedweg ; Drive-by-shooting ; Elsen, Inge; Gabriëlle, Maria ; Ganahl, Rainer ; De Graef, Rudy ; Gross, Ulrikke ; Haveman, Nina ; Heath, Claude ; Holzfeind, Heidrun ; Hravtin, Emil ; Jacobs, Henri ; Jennes, Dirk ; Kaaserer, Ruth ; Kielczynska, Kinga ; Klub Zwei ; Kooijmans, Jeroen ; Krenn, Martin ; Leestemaker, Johan ; Loots, Hilde ; Maes, Ives ; Magee, Micah ; Mertens, Pierre ; Naveau, Nadia ; Nelleman-Poulsen, Tanja ; Nerwen, Diane ; Nys, Tom ; Oosting, Alien ; Panhuysen, Paul ; Perlin, Jenny ; Poloni, Marco ; Radovanic, Goran ; Ressler, Oliver ; Rivera, Alex ; Rivera, Julia ; Robijns, Gert ; Rogiers, Peter ; Salazar, Pepo ; Satorre, Jorge ; Staka, Andreas ; Van Bergen, Jeroen ; Van Dingenen, Filip ; Van Robays, Nele ; Van Snick, Philippe ; Vanden Meersch, Els ; Vansteenwegen, Elke ; Vietà, Mayte ; Visch, Henk ; Vrancken, Kristof ; Winterling, Susanne
kunstcatalogus